Assessment of Bank Health Levels using RGEC Methods on National Private Public Banks - Setiadi, Pompong B; S., Ratna Ursula (International Journal of Social and Administrative Sciences, 2020)
This study aims to determine the level of health of National Private Commercial Banks by using standards set by Central Bank, namely by using the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method. The period used in this study began in 2016 until 2018. The object of this study was National Private Commercial Banks. This study uses data analysis with ratio analysis: (1) Risk Profile using the NPL ratio (Non-Performing Loan), IRR (Interest Rate Risk) and LDR (Loan to Deposit Ratio), (2) Good Corporate Governance (GCG), (3) Earnings using ROA (Return On Assets) and NIM ratios (Net Interest Margin), and (4) Capital using CAR (Capital Adequacy Ratio) financial ratio. The results of the study during the period 2016 to 2018 show that: (1) Risk Profile aspects of National Private Commercial Banks are very healthy condition with NPL ratios of 0.31%, 0.24%, and 0.19%, respectively. for IRR of 151.30%, 166.94% and 159.30%, and for LDR of 81.26%, 89.68% and 85.16%. (2) GCG aspects show 1.925, 1.925 and 1.85 with healthy criteria. (3) Earnings Aspect shows a healthy condition with ROA values of 2.10%, 2.01%, and 1.34% and NIM shows 4.9%, 5.2%, and 4.7%. (4) Capital aspects show very healthy conditions with CAR values of 9.69%, 11.59%, and 11.43%. (5) The RGEC aspect shows a Composite rating 1 (PK-1) with very healthy criteria.